Psikanaliz Kuramının Yükselen Hermenötik Değeri - Hasan Kaplan (Dini Araştırmalar, 2015)
Sigmund Freud and his theory of psychoanalysis have been going under the intensive scientific inquisitions for many decades and it appears that this will last for many decades to come. Providing a brief overview of the development of the psychoanalytic theory and the debates for and against it, this paper tries to bring attentions to the psychoanalysis as an interpretative enterprise. Drawing on tire recent trend in the Continental philosophy, it argues that even though it has lost its popularity in academic psychology, psychoanalysis has been gaining a new recognition in Humanities as an art of interoperation. In this context, the value of psychoanalysis as “hermeneutics of suspicion” is discussed